2023
DOI: 10.1021/acsomega.2c07818
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Approach of Using Arundo donax Leaves Reinforced Cement Mortar/Fly Bottom Ash Composites

Abstract: Earlier research suggested using ash to substitute cement, whereas other studies looked at the possibility of using plant-derived agricultural wastes as fiber reinforcement in cement applications. This study offered an environmentally friendly option to change traditional mortars by replacing cement with fly bottom ash (FBA) waste at 10, 20, 30, and 40 wt %. Likewise, Arundo donax leaves (ADL) were employed to reinforce the modified cement mortars at 0.4, 2, 5, and 7 wt %. X-ray diffraction analysis of used ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…The FS for the CEMA10 sample was lower than that for CEMA0 by 2.5%, 11.2%, and 16.1% at 2, 7, and 28 days, respectively. A comparable pattern was noticed when the agricultural waste ash substitution for cement exceeded 10%, where the FS flexural strength decreased due to the high porosity of the ash in the cement mixes [2].…”
Section: Flexural Strengthsupporting
confidence: 65%
See 2 more Smart Citations
“…The FS for the CEMA10 sample was lower than that for CEMA0 by 2.5%, 11.2%, and 16.1% at 2, 7, and 28 days, respectively. A comparable pattern was noticed when the agricultural waste ash substitution for cement exceeded 10%, where the FS flexural strength decreased due to the high porosity of the ash in the cement mixes [2].…”
Section: Flexural Strengthsupporting
confidence: 65%
“…The escalating demand for cement-based materials in the wake of rapid urbanization and infrastructural development has increased cement consumption and production worldwide [1]. However, the cement-manufacturing industries are considered the primary contributors to global warming, accounting for approximately 8% of worldwide anthropogenic CO 2 emissions [2]. As such, large amounts of CO 2 are emitted during material transportation, grinding, and crushing, lime production, fuel consumption, and the calcination of limestone [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eslami, A. et All [12] explored palm fibers to enhance traditional adobe bricks, with varying optimal contents for different properties. In the research conducted by Hachem, H et All [13], they explored the use of fly bottom ash (FBA) waste and Arundo donax leaves (ADL) as alternatives to cement in mortar composites, with the goal of creating more sustainable building materials. They found that FBA reduced density and thermal conductivity while increasing porosity and water absorption.…”
Section: Introductionmentioning
confidence: 99%